Фазовая проницаемость коллекторов в приложении к добыче трудноизвлекаемых запасов - Бажал, А. И.; Бажал, А. А.; Сарафанова, М. А. (My University, 2009)
На основі базових законів фазової проникності досліджуються технологічні підходи до видобутку важкодобувних записів копалин вуглеводородів.

The basic physical laws and quantitative estimations of phase permeability of collectors in the appendix to extraction of stocks which are resulted are difficultly taken.
Keywords: гистерезис смачиваемости пор; капиллярная пропитка; фильтрация; нефтеотдача пластов